Mammografiprogrammet - tidligere, i dag og i fremtiden - Solveig Hofvind; Åsne Sørlien Holen; Gunhild Mangerud (Norsk Forening for Epidemiologi, 2022)
Norsk sammendrag Mammografiprogrammet (engelsk: BreastScreen Norway) er det offentlige screeningprogrammet for brystkreft i Norge. Det startet som et pilotprosjekt i 1995 og ble gradvis landsdekkende frem til 2005. Programmet inviterer alle kvinner i alderen 50-69 år til mammografiscreening hvert annet år. Kreftregisteret har det administrative ansvaret for Mammografiprogrammet, mens screening skjer ved 30 screeningenheter knyttet til 17 spesialiserte brystsentre som har ansvar for diagnostikk, behandling og oppfølging. Mammografiprogrammet støtter seg på kunnskapsbaserte europeiske retningslinjer og anbefalinger. Programmet er stadig gjenstand for debatt, spesielt når det kommer til anslag for reduksjon i brystkreftdødelighet og overdiagnostikk, samt om kvinnene som inviteres tilbys tilstrekkelig informasjon til å ta et informert valg om deltagelse. Mammografiprogrammet har høy oppslutning, om lag 75% av de inviterte møter. Andelen som tilbakekalles etter screening er om lag 3,5%, mens andelen som får diagnostisert brystkreft på bakgrunn av funn på screeningbildene er rundt 0,6% av alle screenede. Målet med Mammografiprogrammet er å redusere dødeligheten av brystkreft gjennom tidlig diagnostikk. Det er også et mål å vedlikeholde og videreutvikle kvaliteten i programmet, og samtidig øke fordelene og redusere ulempene ved deltagelse. Gjennom studier undersøkes blant annet bruken av nye screeningteknikker som tomosyntese, og muligheter innenfor vurdering av mammografibilder med bruk av kunstig intelligens. Programmet ser også fremover med tanke på utvidelse av målgruppen og mer persontilpasset screening. Alle endringer i Mammografiprogrammet vil og bør være basert på tilgjengelig kunnskap og forskning. Engelsk sammendrag BreastScreen Norway targets women aged 50 to 69 years for mammography screening every other year. The program started as a pilot project in 1995, was gradually expanded and became nationwide from 2005. Internationally, the history of mammography screening started in the early 1960s, when the first randomized trial in New York began. At that time, breast cancer patients had poor survival. Now, more than 50 years later, organized mammography screening is a highly evaluated and quality assured health care service in Norway and internationally. In Norway, an essential part of building the nationwide screening program was the establishment of specialized breast centers, with a focus on efficient workflow, centralized professional competence, and multidisciplinary teamwork. Another key factor in the program is the invitation system, which is based on personal invitations with scheduled appointments automatically sent to all women in the target group. The invitation system facilitates regular participation regardless of where women live. The Norwegian model for breast screening is based on a centralized database and a shared IT system, which creates distinct opportunities for communication, quality assurance, and research. This ensures complete data and individual follow-up, and has been a successful model that is quite unique internationally. It is well known that the concept of mammography screening has spurred debates about its potential benefits and harms during the past decades, especially related to reduced breast cancer mortality and overdiagnosis, and the ethical question whether invited women are offered sufficient information to make an informed choice about participation. In recent years, international publications have strengthened the evidence for mammography screening. BreastScreen Norway relies on evidence-based European guidelines and recommendations, which conclude that there is sufficient evidence to support the benefits of mammography screening for women aged 50-69. BreastScreen Norway has a high attendance with an annual participation rate of 75%. The proportion of women recalled for further assessment is about 3.5%, while the rate of screen-detected cancer due to suspicious findings on mammography is around 0.6% of all screened. The main goal of BreastScreen Norway is to reduce breast cancer mortality through early detection. Another goal is to maintain and further develop the quality of the program, increase the benefits and reduce the harms of participating in the program. Through studies, the use of new screening methods, such as tomosynthesis, and new methods for assessing screening mammograms using artificial intelligence, are investigated. Important future perspectives of the program are related to expanding the age group and personalized screening. Changes in the program will and should be evidence-based and extensive research is needed to fill knowledge gaps before actions can be taken.